2021
DOI: 10.1038/s41392-021-00716-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased inhibition of exosomal miRNAs on SARS-CoV-2 replication underlies poor outcomes in elderly people and diabetic patients

Abstract: Elderly people and patients with comorbidities are at higher risk of COVID-19 infection, resulting in severe complications and high mortality. However, the underlying mechanisms are unclear. In this study, we investigate whether miRNAs in serum exosomes can exert antiviral functions and affect the response to COVID-19 in the elderly and people with diabetes. First, we identified four miRNAs (miR-7-5p, miR-24-3p, miR-145-5p and miR-223-3p) through high-throughput sequencing and quantitative real-time PCR analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 36 publications
2
61
0
Order By: Relevance
“…Likewise, Wang et al (2021) analyzed serum samples of both T2D patients and elderly people and observed that the expression levels of miR-7-5p, miR-24-3p, miR-145-5p, and miR-223-3p were decreased in those individuals; however, this altered miRNA expression was not observed in young people. Since it was unveiled that both the free form and the exosome form of the aforesaid miRNAs might hinder the replication of the SARS-CoV-2 via targeting the S protein, this regulatory mechanism was negatively affected in T2D patients and elderly persons due to their low circulating levels of the miRNAs at issue; therefore, these individuals are more vulnerable to SARS-CoV-2 infection.…”
Section: Studies On Comorbiditiesmentioning
confidence: 99%
“…Likewise, Wang et al (2021) analyzed serum samples of both T2D patients and elderly people and observed that the expression levels of miR-7-5p, miR-24-3p, miR-145-5p, and miR-223-3p were decreased in those individuals; however, this altered miRNA expression was not observed in young people. Since it was unveiled that both the free form and the exosome form of the aforesaid miRNAs might hinder the replication of the SARS-CoV-2 via targeting the S protein, this regulatory mechanism was negatively affected in T2D patients and elderly persons due to their low circulating levels of the miRNAs at issue; therefore, these individuals are more vulnerable to SARS-CoV-2 infection.…”
Section: Studies On Comorbiditiesmentioning
confidence: 99%
“…[ ] y) miR-223-3p: significantly downregulated in COVID-19 [1800]. [ ] z) miR-150-5p: significantly downregulated in COVID-19 [1637].…”
Section: [P-5]mentioning
confidence: 99%
“…[ ] ac) miR-15b-5p, miR-486-3p and miR-486-5p upregulated only in severe COVID-19 patient [1627]. [ ] ad) miR-7-5p, miR-24-3p, miR-145-5p and miR-223-3p: are reported to be markedly decreased in the elderly and diabetic groups which have the capability to inhibit S protein expression and SARS-CoV-2 replication [1800]. [ ] ae) miR-17, miR-574-5p, and miR-214: are shown to induce degradation of the S glycoprotein, N and M proteins, and ORF1a of SARS-COV-2.…”
Section: [P-5]mentioning
confidence: 99%
See 2 more Smart Citations